The meaning of ta’awun in boarding school life: An interpretative phenomenological perspective - Na'imah, Tri; Azzahra, Nabilla Feylisha; Septyningtyas, Devi Jati; M Suud, Fitriah; Tahir, Kartini Radjabulan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study addressed the limited number of in-depth investigations into the lived meaning of ta’awun among students in Islamic boarding schools, despite its crucial role in shaping their social and spiritual character. Using a qualitative phenomenological approach, this research explored how students experience and interpret ta’awun in their daily dormitory life. Six students, who had lived for two to five years in a Muhammadiyah boarding school in Banyumas, Central Java, participated in semi-structured interviews lasting 45–60 minutes. Data were analysed ideographically and subsequently synthesized across cases using Interpretative Phenomenological Analysis (IPA). The findings revealed complementary interpretations of ta’awun, as emotional regulation through empathy, as worship that fosters sincerity and inner calm, as mediation in conflict resolution, and as a means of strengthening ukhuwah and social inclusivity. The cross-case synthesis illustrated ta’awun as an evolving spiritual–emotional process, beginning with worship that cultivates sincerity, followed by emotional regulation facilitating relational mediation, leading to social inclusion and ukhuwah, and ultimately culminating in social harmony and inner tranquillity. Overall, ta’awun is not merely an act of helping but a continuous process that fosters emotional balance and restores social relationships within the dormitory context. Islamic values, collective awareness, and group identity serve as the foundation sustaining consistent prosocial behavior. This study deepened the phenomenological understanding of ta’awun as a form of lived spirituality that integrates faith, emotional regulation, and communal restoration. Future studies are encouraged to examine other educational contexts to expand its transferability and relevance for character education grounded in Islamic values